2023
DOI: 10.1101/2023.09.11.557257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic categorization rules alter representations in human visual cortex

Margaret M. Henderson,
John T. Serences,
Nuttida Rungratsameetaweemana

Abstract: Everyday visual search tasks require objects to be categorized according to behavioral goals. For example, when searching for an apple at the supermarket, one might first find the Granny Smith apples by separating all visible apples into the categories “green” and “non-green”. However, suddenly remembering that your family actually likes Fuji apples would necessitate reconfiguring the boundary to separate “red” from “red-yellow” objects. Despite this need for flexibility, prior research on categorization has l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…The possibility that aspects of complex computations, typically ascribed to higher cortical areas, may also occur in lower-level areas challenges the prevailing notion of the cognitive limitations of lower-level areas. Building in representational redundancies throughout cortical hierarchies allows for complex computations to occur in both lower sensory areas and higher-level areas [25, 41, 42]. This mechanism enhances the robustness of representations and facilitates efficient processing, enabled by top-down feedback signals guiding multiplexing in sensory areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that aspects of complex computations, typically ascribed to higher cortical areas, may also occur in lower-level areas challenges the prevailing notion of the cognitive limitations of lower-level areas. Building in representational redundancies throughout cortical hierarchies allows for complex computations to occur in both lower sensory areas and higher-level areas [25, 41, 42]. This mechanism enhances the robustness of representations and facilitates efficient processing, enabled by top-down feedback signals guiding multiplexing in sensory areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent to which lower cortical areas contribute to this adaptive process is not well understood. Past works have shown that responses within sensory areas could be modulated by top-down signals such as selective attention [1625], and that non-sensory information such as memory content can be decoded from activity within sensory areas [2629]. Yet, it remains poorly understood how these neural codes complement computations that take place in higher cortical areas.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, for all analyses, we did not observe generalization between visually evoked responses in this localizer and the preview trials of the main task. This may be due to insufficient statistical power to detect such a generalization or that different features were relevant to discriminate objects in the periphery for quick guidance of eye movements and comparing objects to their memorized size in this localizer task, resulting in less overlap across tasks (Henderson et al, 2023; McKee et al, 2014). Another possibility is that preparatory activity in our task was overall less sensory-like (Gong et al, 2022).…”
Section: Methodsmentioning
confidence: 97%